Amphipoda (Crustacea) from Palau, Micronesia: Families Maeridae and Melitidae - Myers, A.a. (Zootaxa, 2016)
Seven species of senticaudate amphipods belonging to the families Maeridae and Melitidae are recorded from Palau, Federated States of Micronesia, and are figured. Three species are new to science and are fully described and figured.